2020
DOI: 10.1182/blood-2020-134391
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I/IIa Study of Lemzoparlimab, a Monoclonal Antibody Targeting CD47, in Patients with Relapsed and/or Refractory Acute Myeloid Leukemia (AML) and Myelodysplastic Syndrome (MDS): Initial Phase I Results

Abstract: Background Lemzoparlimab (also known as TJC4 or TJ011133), a novel, RBC-sparing CD47 antibody with a unique epitope, is in early phase clinical development in both the U.S. and China. Like other anti-CD47 antibodies, lemzoparlimab blocks the interaction of CD47 and SIRPα, leading to phagocytosis of various CD47+ tumor cell lines and primary AML cells. Mono-treatment of lemzoparlimab inhibited tumor growth completely and extended the overall survival of treated mice in a patient-derived AML xenog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…TJC4 barely affected the hemoglobin and other blood indexes in the tested animals, showing significantly better safety than 5F9. Compared to the CD47 mAb 5F9, TJC4 binds more weakly to human erythrocytes and does not cause HA [ 70 ]. Initial results of lemzoparlimab (NCT04202003) in phase I/IIa study indicated a well-tolerated safety profile with certain clinical efficacy among 5 R/R AML and MDS patients with 2–4 prior therapies.…”
Section: The Clinical Development Of Anti-cd47 Mabs In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…TJC4 barely affected the hemoglobin and other blood indexes in the tested animals, showing significantly better safety than 5F9. Compared to the CD47 mAb 5F9, TJC4 binds more weakly to human erythrocytes and does not cause HA [ 70 ]. Initial results of lemzoparlimab (NCT04202003) in phase I/IIa study indicated a well-tolerated safety profile with certain clinical efficacy among 5 R/R AML and MDS patients with 2–4 prior therapies.…”
Section: The Clinical Development Of Anti-cd47 Mabs In Chinamentioning
confidence: 99%
“…Initial results of lemzoparlimab (NCT04202003) in phase I/IIa study indicated a well-tolerated safety profile with certain clinical efficacy among 5 R/R AML and MDS patients with 2–4 prior therapies. Of special note, one patient with primary refractory AML achieved morphologic leukemia-free state (MLFS) after 2 cycles of lemzoparlimab treatment at 1 mg/kg [ 70 ].…”
Section: The Clinical Development Of Anti-cd47 Mabs In Chinamentioning
confidence: 99%
“…In addition, three out of seven patients had a CR, one had a partial response, and three achieved stable disease. In an ongoing phase I/II clinical trial (NCT04202003), r/r AML and MDS patients were treated with monotherapy of Lemzoparlimab [ 208 ]. Most adverse events were grade I or II, but one patient experienced grade III thrombocytopenia.…”
Section: Targeting Cd47-sirpα To Potentiate Antibody Therapymentioning
confidence: 99%
“…In line with this, deglycosylation by peptide‐N‐glycosidase (PNGase) treatment restored RBC binding 27 . Of these next‐generation antibodies, clinical results have only been reported for lemzoparlimab and AK117, with no serious haematological adverse effects or DLTs observed in lemzoparlimab doses up to 20–30 mg/kg weekly 28 . Treatment with AK117 similarly did not associate with haematological adverse effects, even up to 20 mg/kg.…”
Section: Strategies To Reduce the Interaction Of Cd47/sirpα Blockers ...mentioning
confidence: 81%